Mapping ethics self-regulation within political parties: Norms, oversight and enforcement - Sousa, Luis de (2022)
This article introduces the new Party Ethics Self-Regulation database, covering 21 indicators on ethics self-regulation organised into three categories (norms, oversight and enforcement) across 200 political parties of 25 countries available in 2020. Internal self-regulatory efforts developed by political parties have been insufficiently addressed in the literature and remain a blind spot in existing databases on political parties. Our analyses indicate that Radical Right Parties have a lower probability of adopting codes of conduct/ethics when compared to any other party family. It also reveals the strongest effect of country-level factors, with party system institutionalization, political corruption or level of democracy shaping the adoption of at least one form of ethics regulation/body. These findings are relevant because they open the debate about the possibility of incrementing ethics self-regulation within political parties through ethics-targeted public funding and raise the need for further research on the effects of such measures on the parties’ ethical climate and public legitimation.